Proceedings of Eurosensors 2017, Paris, France, 3–6 September 2017 2017
DOI: 10.3390/proceedings1040615
|View full text |Cite
|
Sign up to set email alerts
|

A Flexible Pad-Printed Fluxgate Sensor

Abstract: A flexible flat micro-Fluxgate sensor with amorphous rectangular core, fabricated using a simple printing technique is presented. All materials were selected to facilitate the fabrication process and to achieve optimal sensor performance. The device's response to an externally applied magnetic field has been studied. The linear measuring range of the sensor is approximately ±40 μT with a linearity error of <2% FS at 100 kHz excitation frequency, allowing the measurement of the terrestrial magnetic field. Exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
5
1
Order By: Relevance
“…Findings from this study have also shown that the linear response of the device to an external applied magnetic field was 60µT at 3.478V and 70µT at 3.136V for the designed fluxgate sensor with MFB-BPF and SK-BPF respectively at 7.07Hz excitation frequency. This finding is quite different from that of [17] who obtained a linear sensor response of ±40µT at 100kHz excitation frequency while working on a flexible flat micro-fluxgate sensor with amorphous rectangular core, using a simple pad-printing technique. Based on the results obtained from the investigations of the two BPF's, the performance response of the MFB-BPF is better than that of the SK-BPF and hence, it adoption for the design and development of the high sensitive fluxgate sensor for earth magnetic field exploration.…”
Section: Discussioncontrasting
confidence: 99%
“…Findings from this study have also shown that the linear response of the device to an external applied magnetic field was 60µT at 3.478V and 70µT at 3.136V for the designed fluxgate sensor with MFB-BPF and SK-BPF respectively at 7.07Hz excitation frequency. This finding is quite different from that of [17] who obtained a linear sensor response of ±40µT at 100kHz excitation frequency while working on a flexible flat micro-fluxgate sensor with amorphous rectangular core, using a simple pad-printing technique. Based on the results obtained from the investigations of the two BPF's, the performance response of the MFB-BPF is better than that of the SK-BPF and hence, it adoption for the design and development of the high sensitive fluxgate sensor for earth magnetic field exploration.…”
Section: Discussioncontrasting
confidence: 99%
“…[21][22][23] The technology can be used to detect WMF and has a high precision. 24 Thus, in this article, the technology is first introduced to detect the WMF to obtain the roller speed and inner raceway speed. Figure 1 shows the detection mechanism of cage slip.…”
Section: Detection Methods Of Cage Slipmentioning
confidence: 99%
“…Schoinas et al reported a flexible, flat, miniaturized fluxgate sensor that was fabricated by the pad/printing technique. , As shown in Figure A(a) and A(b), silver-based inks were used as the conductive tracks, the resin was used for the insulation layer, and a 25 nm thick ribbon from Vitrovac 6025Z (VACUUMSCHMELZE GmbH & Co. KG) was selected for the soft magnetic core and fixed to the insulation layer by an epoxy-based glue. The dimensions of the entire fluxgate sensor were 40 mm × 20 mm × 0.3 mm, fabricated on a 127 μm Kapton substrate.…”
Section: Other Flexible Magnetic Field Sensorsmentioning
confidence: 99%